2015
DOI: 10.1063/1.4934622
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage radio-frequency interferometer sensors

Abstract: We show that simple radio-frequency (RF) interferometers can have slow-wave positive group delay (PGD) or negative group delay (NGD), as well as superluminal propagation (SP) regions, due to a destructive interference process. These properties are easily tunable, which makes RF interferometers unique among systems that have NGD and SP regimes. A two-stage interferometer arrangement, which includes a first stage interferometer in the material-under-test path of a second stage, has significantly improved sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The flow cell forms the sample-under-test (SUT) branch while the tuning branch has a digital tunable attenuator (DTA) and a phase shifter. The basic MIM working principle is described in previous work. The introduction of DTA and computer control are essential for the proposed HPLC measurements.…”
Section: Design Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow cell forms the sample-under-test (SUT) branch while the tuning branch has a digital tunable attenuator (DTA) and a phase shifter. The basic MIM working principle is described in previous work. The introduction of DTA and computer control are essential for the proposed HPLC measurements.…”
Section: Design Considerationmentioning
confidence: 99%
“…In this work, we propose and demonstrate a microwave flow detector technique that is promising to address the RI detector difficulties discussed above. The detector is based on our previous work on microwave interferometers (MIMs). In this study, an electronically tunable MIM is developed and demonstrated for HPLC measurements under isocratic and gradient elution operations. We also show the quantification of coeluted vitamin E succinate (VES) and vitamin D3 (VD3).…”
mentioning
confidence: 99%
“…This article mainly introduces a novel CPW‐based sensor for determining the complex permittivity of MUT. The combination of symmetric circuit structure and IDC configuration improves the measurement accuracy . The theoretical behavior of sensing strategy is also analyzed by taking into consideration an equivalent lumped circuit model.…”
Section: Introductionmentioning
confidence: 99%